2008
DOI: 10.1002/eqe.833
|View full text |Cite
|
Sign up to set email alerts
|

Error estimation of closed‐form solution for annual rate of structural collapse

Abstract: With the increasing emphasis of performance-based earthquake engineering (PBEE) in the engineering community, several investigations have been presented outlining simplified approaches suitable for performance-based seismic design (PBSD). Central to most of these PBSD approaches is the use of closed-form analytical solutions to the probabilistic integral equations representing the rate of exceedance of key performance measures. Situations where such closed-form solutions are not appropriate primarily relate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 17 publications
5
61
0
Order By: Relevance
“…Again the different methods provide similar results (the second moment and Monte Carlo methods are similar, and thus only one is shown), but more importantly it can be seen that the uncertainty in the collapse probability has been significantly increased when collapse fragility uncertainty is considered. This is in agreement with analytical solutions, which show that the uncertainty in the collapse capacity are the epistemic uncertainty in the collapse capacity and hazard respectively, and k is the log-log slope of the seismic hazard curve (which increases with reducing exceedance probability) (Bradley and Dhakal 2008).…”
Section: U Lnsupporting
confidence: 88%
“…Again the different methods provide similar results (the second moment and Monte Carlo methods are similar, and thus only one is shown), but more importantly it can be seen that the uncertainty in the collapse probability has been significantly increased when collapse fragility uncertainty is considered. This is in agreement with analytical solutions, which show that the uncertainty in the collapse capacity are the epistemic uncertainty in the collapse capacity and hazard respectively, and k is the log-log slope of the seismic hazard curve (which increases with reducing exceedance probability) (Bradley and Dhakal 2008).…”
Section: U Lnsupporting
confidence: 88%
“…(3)). Several authors [14,15,18] have argued that this assumption can lead to inaccurate results. This error can be partly eliminated if the hazard curve is approximated by a second-order polynomial in log-log coordinates, as suggested by Vamvatsikos [15]:…”
Section: Summary Of Basic Assumptions and Limitationsmentioning
confidence: 96%
“…(5)) is useful in order to understand which parameters are the most relevant for seismic risk assessment, although several authors [14,15,18] have found that the closed-form solution of the risk equation can provide inaccurate results. However, assumptions related to the shapes of the fragility function and the hazard function are not the only issues which affect the accuracy of seismic risk assessment according to Eq.…”
Section: Theoretical Background and Derivationsmentioning
confidence: 99%
“…It can be described by a lognormal distribution, where various studies have illustrated that this assumption is adequate for describing a displacement-based engineering demand parameter given IM [37][38][39][40] …”
Section: Nonlinear Analysis Procedures and Resultsmentioning
confidence: 99%